Palinología y geoquímica de la Formación Casa de Piedra, Triásico de la Subcuenca de Rincón Blanco, provincia de San Juan - Macino, Javier (2017)
The Casa de Piedra Formation (Ladinian/Carnian) was deposited in a fluvio-deltaic to lacustrine environment. Chemical analysis of kerogen from levels of total organic carbon. The basal two-thirds of the studied section are dominated by generally low fluorescent amorphous kerogen, and high percentages of yellow fluorescent Botryococcus colonies (kerogen type I). The organic matter displays a relatively high HC/HO index and moderate total hydrocarbons in several horizons constituting a potential source rock. In the upper third of the unit dominates low fluorescent, mostly opaque kerogen, with subordinate wood phytoclasts and miospores (kerogen type III); HC/HO and total hydrocarbons values are low, thus the generation potential of these horizons is reduced. The increase of the K/Rb ratio towards the top of the section, suggests terrigenous origin of the kerogen for these horizons.